Conditions and prospects for the development of small and medium business of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
The Government of the Republic of Kazakhstan is taking significant steps to support and develop business. The regulatory and legal framework for improving the conditions for the development of entrepreneurship, ensuring the protection of rights and legitimate interests of business entities has been formed. Work is underway to improve tax and customs legislation, reduce administrative barriers and improve the procurement system, and create the necessary investment conditions for entrepreneurship.Many entrepreneurs are not aware of the existence of support institutions.Or do not own information about their services. Low awareness of the interested group about theopportunities influences the further development of the business and reduces the level of trust in thesupport institutions, as the result of the activity is not sufficiently distributed.The purpose of the article is to identify problems in the development of small and mediumbusiness in the Republic of Kazakhstan, on the basis of which it is planned to developrecommendations for improving the environment for entrepreneurial activity.The objectives of the work are to identify factors that impede the conduct of business, and to study the effectivenessof institutions supporting entrepreneurship. Institutions are understood as organizations that promotebusiness activities with different forms of ownership. This is the National Chamber of Entrepreneurs(NPP), JSC «Fund for Support of Entrepreneurship» Damu «(Damu), business incubators, and many others.The revealed factors allow to draw a conclusion that institutions for supporting entrepreneurship are veryimportant at this stage of small and medium business development.Cooperation between business and responsible institutions will help to realize the set goals. Thus,entrepreneurship will have access to the best conditions of activity, and the state has more taxes to thebudget, and the solution of many socially significant and socio-economic problems. To date, the problemis that due to various reasons, such as mistrust, lack of advocacy, cultural and behavioral barriers andother people demonstrate low awareness of the activities of business support institutions.